Determination of Effective Moisture Diffusivity Considering Shrinkage for Vibration-Assisted Infrared Drying of Pumpkin - Jiraporn Sripinyowanich Jongyingcharoen; Worawit Naweera; Sakawrat Sangruangnak; Achira Assawadejmethakul (BIO Web of Conferences, 2025)
Drying characteristics and physical properties of pumpkin slices during vibration-assisted infrared (VIR), infrared (IR), and hot air (HA) drying were investigated. VIR drying exhibited the highest drying rate (0.1 g water/g dry matter·min) and shortest drying time (100 min), with drying efficiency influenced by IR intensity. Pumpkin slices dried under VIR drying at a middle IR intensity of 750 W/m² demonstrated superior product properties. Shrinkage was linearly correlated with moisture ratio. Effective moisture diffusivity (D eff ) ranged from 1.44×10 -8 to 5.78×10 -8 m 2 /s for HA and VIR drying, respectively. Incorporating shrinkage effects, D eff-S decreased linearly with decreasing moisture ratio. D eff-S exhibited a strong negative correlation with shrinkage and a strong positive correlation with moisture content, moisture ratio, projected area, and volume.
Keywords: Food Drying and Modeling; Freezing and Crystallization Processes; Microencapsulation and Drying Processes